Comparison of Mesenchymal Stem Cells Isolated From Pulp and Periodontal Ligament. Issue 2 (1st February 2015) - Hakki, Sema S.; Kayis, Seyit Ali; Hakki, Erdogan E.; Bozkurt, S. Buket; Duruksu, Gokhan; Unal, Zehra Seda; Turaç, Gizem; Karaoz, Erdal
Abstract : Background: Cell‐based therapy using mesenchymal stem cells (MSCs) seems promising to obtain regeneration of dental tissues. A comparison of tissue sources, including periodontal ligament (PDL) versus pulp (P), could provide critical information to select an appropriate MSC population for designing predictable regenerative therapies. The purpose of this study is to compare the proliferation and stemness and the MSC‐specific and mineralized tissue–specific gene expression of P‐MSCs and PDL‐MSCs. Methods: MSCs were obtained from PDL and P tissue of premolars (n = 3) extracted for orthodontic reasons. MSC proliferation was evaluated using a real‐time cell analyzer for 160 hours. Telomerase activity was evaluated by a telomeric repeat amplification protocol assay based on enzyme‐linked immunosorbent assay. Total RNA was isolated from the MSCs on day 3. A polymerase chain reaction (PCR) array was used to compare the expression of MSC‐specific genes. The expression of mineralized tissue‐associated genes, including Type I collagen ( COL I ), runt‐related transcription factor 2 ( RunX2 ), bone sialoprotein ( BSP ), and osteocalcin ( OCN ) messenger RNA (mRNA), was evaluated using quantitative real‐time PCR. Results: Higher proliferation potential and telomerase activity were observed in the P‐MSCs compared to PDL‐MSCs of premolar teeth. Fourteen of 84 genes related to MSCs were expressed differently in the PDL‐MSCs versus the P‐MSCs. The expressions of bone morphogenetic protein 2 ( BMP2 ) and BMP6 ; sex‐determining region Y‐box 9 (SOX9); integrin, alpha 6 (ITGA6); melanoma cell adhesion molecule ( MCAM ); phosphatidylinositol glycan anchor biosynthesis, class S ( PIGS ); prominin 1 ( PROM1 ); ribosomal protein L13A ( RPL13A ); and microphthalmia‐associated transcription factor ( MITF ) were higher in the P‐MSCs compared to the PDL‐MSCs, and higher expression of matrix metalloproteinase 2 ( MMP2 ), interleukin ( IL )‐6, insulin ( INS ), alanyl (membrane) aminopeptidase ( ANPEP ), and IL‐10 were observed in the PDL‐MSCs. However, there was no statistically significant difference in the expression of mineralized tissue–associated genes, including BSP and RunX2, between the P‐MSCs and the PDL‐MSCs. Higher expression of COL I and lower expression of OCN mRNA transcripts were noted in the PDL‐MSCs compared to the P‐MSCs. Conclusions: The results of this study suggest that MSCs isolated from P and PDL tissues show different cellular behavior. To increase the predictability of MSC‐based regenerative treatment, differences in dental tissue–derived MSCs and favorable aspects of cell sources should be further clarified.